Pengaruh Formula Pakan terhadap Pertumbuhan Larva Hermetia illucens dalam Biokonversi Limbah Organik - Hartati, Hartati; Jumadi, Oslan; Junda, Muhammad; Kurnia, Nani; Sahribulan, Sahribulan; Saparuddin, Saparuddin; Djawad, Yasser Abd; Harianto, Fajar; Yanti, Christie Novri (Fakultas MIPA UNM, 2021)
Abstract. The growth rate of Hermetia illucens larvae in the bioconversion of organic waste is influenced by the media and environmental conditions where the BSF lives. This study aims to determine the effect of the feed formula on the growth of Hermetia illucens larvae in the bioconversion of organic waste. This research method was carried out by rearing BSF larvae, making BSF feed formulas, determining larval length, determining the weight and weight of BSF cassava. The results showed that the feeding formula from fish waste, tapioca waste with a chopped diameter of 10,20,30 mm gave a significant effect on the growth of BSF larvae (larval length, larvae weight) and BSF maggots. The provision of 20 and 30 percent fish waste has a higher weight and length with a chopped diameter of 20 and 30 mm..Keywords: feed formula, hermetia illucens, bioconversion, organic waste